Academic Approach for Religious Radicalism - Akhmad Siddiq (Graduate Program of Pontianak Institute of Islamic Studies, 2019)
Blaming or demonizing other could appear from misunderstanding paradigm toward knowledgeable entities: individually or collectively. Inclusive approach to know and understand other religious groups is a basic principle to build interreligious relation. In his Dialogue Decalogue, Leonard Swidler suggests that to build interfaith dialogue is to learn and understand (other) realities. In this regard, religious radicalism could be perceived as an outcome of misunderstanding that allows people to exclude or ignore others. This paper aims to explore several books of Muslim scholars, both in classical and contemporary period, relating to comparative study of religion. It is the finding of this work that understanding other religions (or religious others) as articulated in the book will create a level of acceptance within religious believers.